Generation of a substance with negative mass - Golovkin, BG (Annals of Mathematics and Physics, 2024)
An analysis of known experiments was carried out to determine the dependence of the mass of electrons on their speed. Errors were discovered in determining the sign of the electron mass. It is shown that at electron velocities above the critical ω = 235696.8871 km/s their masses are negative. The results obtained are explained on the basis of the Principle of Nonequivalence of inertial and gravitational masses since inertial mass can only be positive, and gravitational mass can only be positive or negative The purpose of this work is to show that since radioactive substances can emit electrons with negative mass at velocities above ω, they can be a source of their production.